First Chromosomal Analysis in Hepsetidae (Actinopterygii, Characiformes): Insights into Relationship between African and Neotropical Fish Groups - Carvalho, Pedro C.; Oliveira, Ezequiel A. de; Bertollo, Luiz A. C.; Yano, Cassia F.; Oliveira, Claudio [UNESP]; Decru, Eva; Jegede, Oladele I.; Hatanaka, Terumi; Liehr, Thomas; Al-Rikabi, Ahmed B. H.; Cioffi, Marcelo de B. (Frontiers Media Sa, 2017)
Hepsetidae is a small fish family with only the genus Hepsetus, with six described species distributed throughout the South, Central and Western regions of Africa, showing a close relationship with the Alestidae and some Neotropical fish families. However, no cytogenetic information is available for both Hepsetidae and Alestidae species, thus preventing any evolutionary comparative studies at the chromosomal level. In the present study, we are providing new cytogenetic data for Hepsetus odoe, including the standard karyotype, C-banding, repetitive DNAs mapping, comparative genomic hybridization (CGH) and whole chromosome painting (WCP), providing chromosomal patterns and subsidies for comparative cytogenetics with other characiform families. Both males and females H. odoe have 2n = 58 chromosomes (10m + 28sm + 20st/a), with most of the C-band positive heterochromatin localized in the centromeric and subtelomeric regions. Only one pair of chromosomes bears proximal 5S rDNA sites in the short arms, contrasting with the 18S rDNA sequences which are located in the terminal regions of four chromosome pairs. Clear interstitial hybridization signals are evidenced for the U1 and U2 snDNA probes, but in only one and two chromosome pairs, respectively. Microsatellite motifs are widely distributed in the karyotype, with exception for the (CGG)(10), (GAA)(10) and (GAG)(10) probes, which highlight conspicuous interstitial signals on an unique pair of chromosomes. Comparative data from conventional and molecular cytogenetics, including CGH and WCP experiments, indicate that H. odoe and some Erythrinidae species, particularly Erythrinus erythrinus, share similar chromosomal sequences suggesting some relatedness among them, although bearing genomic specificities in view of their divergent evolutionary histories.
Keywords: fishes; molecular cytogenetics; chromosomal painting; comparative genomic hybridization (CGH); karyotype evolution